Direct acute tubular damage contributes to Shigatoxin‐mediated kidney failure. Issue 1 (25th July 2014) - Porubsky, Stefan; Federico, Giuseppina; Müthing, Johannes; Jennemann, Richard; Gretz, Norbert; Büttner, Stefan; Obermüller, Nicholas; Jung, Oliver; Hauser, Ingeborg A; Gröne, Elisabeth; Geiger, Helmut; Gröne, Hermann‐Josef; et al.
Abstract The pathogenesis and therapy of Shigatoxin 2 (Stx2)‐mediated kidney failure remain controversial. Our aim was to test whether, during an infection with Stx2‐producing E. coli (STEC), Stx2 exerts direct effects on renal tubular epithelium and thereby possibly contributes to acute renal failure. Mice represent a suitable model because they, like humans, express the Stx2‐receptor Gb3 in the tubular epithelium but, in contrast to humans, not in glomerular endothelia, and are thus free of glomerular thrombotic microangiopathy (TMA). In wild‐type mice, Stx2 caused acute tubular dysfunction with consequent electrolyte disturbance, which was most likely the cause of death. Tubule‐specific depletion of Gb3 protected the mice from acute renal failure. In vitro, Stx2 induced secretion of proinflammatory cytokines and apoptosis in human tubular epithelial cells, thus implicating a direct effect of Stx2 on the tubular epithelium. To correlate these results to human disease, kidney biopsies and outcome were analysed in patients with Stx2‐associated kidney failure (n = 11, aged 22–44 years). The majority of kidney biopsies showed different stages of an ongoing TMA; however, no glomerular complement activation could be demonstrated. All biopsies, including those without TMA, showed severe acute tubular damage. Due to these findings, patients were treated with supportive therapy without complement‐inhibiting antibodies (eculizumab) or immunoadsorption. Despite the severity of the initial disease [creatinine 6.34 (1.31–17.60) mg/dl, lactate dehydrogenase 1944 (753–2792) U/l, platelets 33 (19–124)/nl and haemoglobin 6.2 (5.2–7.8) g/dl; median (range)], all patients were discharged after 33 (range 19–43) days with no neurological symptoms and no dialysis requirement [creatinine 1.39 (range 0.84–2.86) mg/dl]. The creatinine decreased further to 0.90 (range 0.66–1.27) mg/dl after 24 months. Based on these data, one may surmise that acute tubular damage represents a separate pathophysiological mechanism, importantly contributing to Stx2‐mediated acute kidney failure. Specifically in young adults, an excellent outcome can be achieved by supportive therapy only. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.